Nanotechnology-enhanced tissue engineering in reconstructive abdominal surgery-a new era in mesh integration and vascularized composite allotransplantation: a systematic review - Vera, Mateo Daniel Fabara; Veloz, Bryan Andrés Andrade; Cutiopala, David Patricio Alulema; Lopez, Jorge Eduardo Maldonado; Cruz, Evelyn Dufay Mendoza; Romero, Evelyn Michelle Sánchez; Peña, Jose Alberto Naspud; Aguilar, Andrea Alejandra Pérez (International Journal of Research in Medical Sciences, 2024)
Nanotechnology-enhanced tissue engineering represents groundbreaking shift of reconstructive abdominal surgery and in mesh integration and vascularized composite allotransplantation (VCA). We explore nanomaterial’s role in this review and investigate how it improves biocompatibility, strength, and functional performance of synthetic meshes as well as their impact on reducing complications such as mesh rejection and infection. Current data suggests nanoscale modifications to mesh surfaces promote cellular adhesion and angiogenesis, reduce inflammatory responses, and is paradigm shift from traditional approaches. Advancements in nanotechnology can revolutionize VCA by enhancing tissue regeneration and improve vascularization and reducing immunosuppressive needs post-transplantation. Statistics reveal complications from conventional mesh repairs such as hernia recurrence occur in up to 30% of cases. Early trials using nano meshes have demonstrated a reduction in recurrence rates to below 15%. Nanotechnology’s integration into VCA could address critical limitations of donor tissue viability with experimental models showing improved graft survival and function. We synthesize latest clinical studies, experimental trials, and meta-analyses to evaluate nanotechnology’s current efficacy and future potential in abdominal reconstructive surgery. While promising these innovations are still nascent, requiring further large-scale clinical validation. We aim to provide comprehensive overview of the most recent advancements and discuss current limitations and future research directions for integrating nanotechnology into reconstructive abdominal surgery while focusing on mesh and VCA applications.